Asbab an-Nuzul: a critical study of the criteria of their acceptability - Fadzil, Ammar (The Islamic Cultural Centre and London Central Mosque, London, 2008)
This article aims to identify criteria for accepting the accounts of asbab an-Nuzul It begins with the definition of asbab an-Nuzul, criteria for accepting asbab an-Nuzul as determined by classical scholars, problems surrounding the reports of asbab an-Nuzul, and ends with suggestions of criteria that should be used and noted when identifying the correct and acceptable accounts of asbab an-Nuzul.